BUDAYA TORAJA DALAM PEMBELAJARAN BAHASA INDONESIA - Patiung, Dahlia (Idaarah: Jurnal Manajemen Pendidikan, 2017)
This study aims to examine in depth about the application of Toraja cultural values in learning Indonesian language in North Toraja District. The method used in this research is descriptive qualitative method. In the data collection, researchers directly involved observing the phenomena that occur in Indonesian language learning in North Toraja State Senior High School. Technique of data collection is done by observation, recording, documentation, and interview. Data analysis was done by data flow model analysis technique.The results showed that the application of Toraja cultural values in Indonesian language learning in SMA Toraja has built the values of Kasiuluran (kinship), tengko situru '(togetherness), kabassaran (work ethic), sikamali' (love), kapa ' patonganan (religious), siri '(shame), and the value menghangkegi'to mendadianna (devotion children to parents).